IMPROVING STUDENTS' READING COMPREHENSION USING COLLABORATIVE STRATEGIC READING (CSR) AT THE EIGHTH GRADE STUDENTS OF SMP NEGERI 1 TAPA - R Agi, Sarina; Otoluwa, Moon Hidayati; Luwiti, Sri Rumiyatiningsih (Jurnal Bahasa, Sastra, dan Budaya, 2022)
This research aims to find out the using Collaborative Strategic Reading (CSR) strategies can improve students' reading comprehension in eighth-grade students of SMP Negeri 1 Tapa. Specifically, it attempted to address the following question: Can the use of Collaborative Strategic Reading (CSR) strategy improve students' reading comprehension at the eighth-grade students of SMP Negeri 1 Tapa. This research conducts quantitatively and uses pre-experimental research. The sample of this research is 20 students of class VIII-6 in the eighth grade of SMP Negeri 1 Tapa in the academic year 2022/2023. A reading comprehension test, specifically descriptive text, is used to collect the data. The test was objective, and it was used to collect the data pre-test and the post-test. The data were analyzed and interpreted using SPSS 26 version. The result of the pre-test was 267, and the post-test was 375. The hypothesis found that a significance value (2-tailed) p = 0.000 0.05. It proves that the Hypothesis (H1) is accepted. Thus, the conclusion is that Collaborative Strategic Reading (CSR) can improve students reading comprehension of the eighth-grade students of SMP Negeri 1 Tapa.